HRCT Chest as an Indispensable Tool for Early Diagnosis of COVID-19: A Retrospective Study - Ahmad, Zubair; Khan, Naseer Ahmad; Arif, Binish; Bhat, Gulzar Ahmad; Dar, Sajjad Ahmad (International Research in Medical and Health Sciences, 2021)
Background: In coronavirus disease-19 (COVID-19), infected people will exhibit mild to moderate respiratory illness. The present study was aimed to evaluate the diagnostic efficacy of High-Resolution Chest Computed Tomography (HRCT) chest findings in tandem with the RT-PCR status in COVID-19 infected patients.Methods: A total of 100 patients visiting the diagnostic imaging centre were subjected to HRCT chest. Subjects who tested negative for HRCT were excluded from the study. Furthermore, the HRCT positive patients were divided into three groups as mild, moderate, and severe depending upon the involvement of lung lobes.Result: Maximum representation (63%) of cases were males and a higher percentage (58%) of patients were older than 60years. 86% of the subjects were in agreement with COVID-19 findings. However, normal findings were present in 14 subjects with suspected COVID-19 infection. Among HRCT positive patients, we observed 81.39% patients with RTPCR positive initially and 13.9% patients turned RT-PCR positive when advised repeat sampling as per strong suspicion on HRCT. Among 86 HRCT positive subjects, 37(43%) were categorised as mild, 29(33.7%) as moderate, and 20(23.3%) were categorised as severe. We observed a higher percentage of cases with lower lung lobe and bilateral lung involvement. Similarly, subpleural Ground Glass Opacities (GGO’s) and vascular enlargement were observed in the majority of subjects with the percentage of 99.3% and 84.0% respectively. Pneumomediastinum occurrence in one (01) patient was one of the interesting findings of the current study.Conclusion: The study shows that HRCT is an indispensable imaging tool to diagnose and categorise the severity of COVID-19 infection for optimum disease management.